A Deixis Analysis of Song Lyrics in Jeremy Zucker's “You Were Good to Me” and “Comethru” - Desy Eva Laila Rokhmah; Dwi Eva Patriciawati Mantiri Santoso (Hasanuddin University, 2022)
This research aims to identify the dominating deixis among the many types of deixis in Jeremy Zucker's songs